Engineering for storage of fruits and vegetables : cold storage, controlled atmosphere storage, modified atmosphere storage - Rao, Chandra Gopala (Academic Press, 2015)
Engineering for Storage of Fruits and Vegetables is a comprehensive reference that provides an understanding of the basic principles of cold storage load estimation, refrigeration capacity calculations for various types of cold storages, and other topics of evaporative cooling, thus demonstrating the important principles for designing low cost precooling chambers. The book is written in an accessible manner to provide a solid understanding of different environments and their considerations to give readers the confidence they need to design suitable packaging materials by understanding parameters, including reaction rates, deteriorative reactions, Arrhenius equations, Q10, K, D, Z parameters, and their influence on reaction rates. Covers a wide variety of related topics, from post-harvest physiology of fruits and vegetables, to the various aspects of controlled atmosphere storages. Explains the application of water activities and enzyme kinetics for predicting shelf life of foods and design of packaging materialsIncludes solved problems and exercises which guide students and assist with comprehension.